Morphological evolution of two-dimensional porous hexagonal trimesic acid framework - Tothadi, Srinu; Koner, Kalipada; Dey, Kaushik; Addicoat, Matthew; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2020)
Hexagonal single crystal structure (Form II) of trimesic acid (TMA) has been isolated by dissolving the interpenetrated Form I of TMA in tetrahydrofuran. Form II (hexagonal) was converted to Form I (interpenetrated) at room temperature through some intermediate structures. A detailed time-dependent FESEM study shows that the external morphology of Form II (hexagonal) is a hollow hexagonal tube that mimics its crystal structure. The block-shaped (morphology) of Form I (interpenetrated) was converted to the hollow hexagonal tube through some intermediate morphologies which are corresponding to particular crystal structures. Here, we have established a strong correlation between crystal structures with the morphology. These hollow tubes have been employed for Rhodamine B dye adsorption studies and showed an uptake of 82%, much more significant than Form I (interpenetrated) (39%) due to the presence of a pore channel in the crystal structure.
Keywords: dye adsorption; hollow hexagonal rod; hydrogen-bonded organic framework; morphology evaluation; trimesic acid